Investigation of sex-specific differences in visual cortical function in a mouse model of syngap1-related intellectual disability - Dedominicis, Luke (The University of Edinburgh, 2025)
SYNGAP1-related intellectual disability is a neurodevelopmental disorder caused by mutations in one copy of the SYNGAP1 gene. It accounts for around 1% of all intellectual disabilities, with a high penetrance of co-morbidities such as epilepsy and autism spectrum disorders. Care giver accounts of the disease symptoms commonly cite atypical sensory perception as one of the symptoms of SYNGAP1-related intellectual disability. Abnormal perception affects the ability of individuals to participate in a shared view of the world and likely underpins some of the difficulties that individuals with intellectual disability and autism spectrum disorders face in social interactions. Increasingly, evidence is supporting sexual differentiation in the severity of symptoms, with girls and women more likely to experience severe sensory processing atypicality and intractable epilepsy in cases where intellectual disability and autism spectrum disorder are co-morbid. Here we attempt to investigate potential sex differences in visual processing using a mouse model of Syngap1 haploinsufficiency. Using 2-photon microscopy and a virally expressed calcium indicator (GCaMP6f) we recorded in-vivo activity of layer 2/3 neurons in the primary visual cortex of female mice whilst they were presented with drifting grating visual stimuli. We quantified the discriminability, selectivity, reliability, depth of modulation, of neuronal population activity in the primary visual cortex of Syngap1 haploinsufficient mice and control littermates. Results obtained from female mice were compared with data previously acquired from male mice using the same methodology. Compared to control littermates, Syngap1+/- mice less reliably encode visual information in primary visual networks of layer 2/3, as measured by the decoding accuracy of visual stimuli, which is reduced in Syngap1+/- mice due to an increase in the variability of neuronal activity. However, no conclusive difference in visual response properties was found between female and male Syngap1 heterozygous mice, indicating that Syngap1 haploinsufficiency produces equivalent deficits in cortical visual processing for both male and female mice.
Keywords: SYNGAP1; Intellectual disability; Visual cortical function; Sex-specific differences; Mouse model